Distinction between hand dominance and hand preference in primates: a behavioral investigation of manual dexterity in nonhuman primates (macaques) and human subjects. Issue 5 (2nd August 2013) - Chatagny, Pauline; Badoud, Simon; Kaeser, Mélanie; Gindrat, Anne‐Dominique; Savidan, Julie; Fregosi, Michela; Moret, Véronique; Roulin, Christine; Schmidlin, Eric; Rouiller, Eric M.
Abstract Background The present study aimed to determine and confront hand preference (hand chosen in priority to perform a manual dexterity task) and hand dominance (hand with best motor performance) in eight macaques (Macaca fascicularis) and in 20 human subjects (10 left‐handers and 10 right‐handers). Methods Four manual dexterity tests have been executed by the monkeys, over several weeks during learning and stable performance phases (in controlled body position): the modified Brinkman board, the reach and grasp drawer, the tube and the bimanual board tasks. Three behavioral tests, adapted versions from the monkeys tasks (modified Brinkman board, tube and bimanual board tasks), as well as a handedness questionnaire, have been conducted in human subjects. Results In monkeys, there was a large disparity across individuals and motor tasks. For hand dominance, two monkeys were rather right lateralized, three monkeys rather left lateralized, whereas in three monkeys, the different parameters measured were not consistent. For hand preference, none of the eight monkeys exhibited a homogeneous lateralization across the four motor tasks. Macaca fascicularis do not exhibit a clear hand preference. Furthermore, hand preference often changed with task repetition, both during training and plateau phases. For human subjects, the hand preference mostly followed the self‐assessment of lateralization by the subjects and the questionnaire (in the latter, right‐handers were more lateralized than left‐handers), except a few discrepancies based on the tube task. There was no hand dominance in seven right‐handers (the other three performed better with the right hand) and in four left‐handers. Five left‐handers showed left‐hand dominance, whereas surprisingly, one left‐hander performed better with the right hand. In the modified Brinkman board task, females performed better than males, right‐handers better than left‐handers. Conclusions The present study argues for a distinction between hand preference and hand dominance, especially in macaque monkeys.